Facile synthesis of BiSI and Bi13S18I2 as stable electrode materials for supercapacitor applications. Issue 38 (10th September 2020) - Sun, Huapeng; Yang, Guiling; Chen, Jie; Kirk, Caroline; Robertson, Neil
Abstract : In this paper, we demonstrate a novel synthetic route of two bismuth chalcogenide materials 3-D hexagonal Bi13 S18 I2 and 3-D orthorhombic BiSI, and investigate their potential as the active electrode material for supercapacitors. Abstract : In this paper, we demonstrate a novel synthetic route of two bismuth chalcogenide materials 3-D hexagonal Bi13 S18 I2 and 3-D orthorhombic BiSI, and investigate their potential as the active electrode material for supercapacitors. Both pure BiSI and Bi13 S18 I2 powders were obtained for the first time at relatively low temperature (120 °C) in a solution system. We studied the effects of different reaction conditions on the surface morphology of the product and found that at a relatively low temperature of 120 °C under atmospheric pressure, the materials can yield smaller crystallite size and higher specific surface area, further increasing the capacitance compared to the synthesis under hydrothermal conditions. Cyclic voltammetry and galvanostatic charge–discharge measurements of the materials were studied using three-electrode and two-electrode configurations at a variety of currents. The galvanostatic charge–discharge measurement results show that the Bi13 S18 I2 electrode has a maximum areal capacitance of 247 mF cm −2 at the current density of 5 mA cm −2 and excellent capacitance retention of 98.4% after 5000 cycles at the current density of 50 mA cm −2 in 3.0 M KOH electrolyte as a two-electrode electrical double-layer capacitor system (EDLC). The BiSI and Bi13 S18 I2 powders have been characterized through PXRD, XPS, Raman spectroscopy, TGA–DSC, BET, SEM and TEM. This facile route to the synthesis of both Bi13 S18 I2 and BiSI with superior stability has promising potential for low-cost and effective electrochemical supercapacitor applications.